Effect of vacuum assisted therapy in wound healing - Ponnoju, Mounika; Uppala, Rajesh; Konda, Varun Deep (International Surgery Journal, 2022)
Background: Vacuum assisted closure (VAC) is a new technique developed in the management of contaminated, acute, and chronic wounds. It refers to wound dressing system that continuously or intermittently apply sub-atmospheric pressure to the surface of a wound which accelerates debridement and promote healing. The optimum pressure for VAC is around 125 mmhg below ambient and this negative pressure helps in removing interstitial fluid, decreases localised edema and increases blood flow. This in turn decreases tissue bacterial levels and promotes wound healing. Methods: Hospital based prospective study. Results: Most common etiology for wounds is diabetes i.e., 50%, Most common organism cultured from wound is Staphylococcus aureus, and least is proteus. Surface area of wound is reduced to <40 cm2 in 76% cases and 7% cases had >60 cm2. After applying VAC dressing 91% of patients had bright red granulation tissue. Mean duration hospital stay was reduced to 10days in patients with VAC dressing. Conclusions: VAC or NPWT therapy is an excellent alternative modality of treatment of acute or chronic large non-healing wounds. It reduces the number of changes of dressing and reduces the time of hospital stay before definitive surgery for covering wound can be planned. Based on the data from the present study and other studies available, VAC appear to result in better and rapid healing and thus a better option of wound management technique.